FAKTOR YANG MEMPENGARUHI KESULITAN DALAM MEMPELAJARI MAKNA KANJI PADA MAHASISWA ANGKATAN 2022 PROGRAM STUDI PENDIDIKAN BAHASA JEPANG UNIVERSITAS RIAU - Ramadhani, Mutia; Basri, Merri Silvia; Yohani, Adisthi Martha (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstrak: Difficulty learning the meaning of kanji is a difficulty for students in learning the meaning of kanji. This study aims to determine the factors of student difficulties in learning the meaning of kanji. This study uses quantitative descriptive methods. This study uses a questionnaire to collect data sources. The respondents in this study were 36 students from the class of 2022 Japanese Language Education FKIP Universias Riau. The results of this study found that there are three factors that have quite an influence on the difficulty of learning the meaning of kanji in students, namely learning strategy factors, curriculum factors and environmental factors.Keywords: Kanji, Meaning, Difficulty.